SOIL NUTRIENT STORAGE UNDER MAJOR ECOSYSTEMS OF COLD DESERTS OF HIMACHAL PRADESH - POONAM; R. BAWA (The Bioscan, 2020)
The present investigation was carried out at Goshal village of Lahaul and Spiti cold desert district of Himachal Pradesh during the year 2014 to compare soil chemical properties in three major ecosystems viz; forest ecosystem, alpine pasture ecosystem and agro ecosystem which have been affected as a result of land use changes . The study area was demarcated into three main ecosystems for conducting soil studies. Average soil nutrient status for all the three ecosystems was studied and our study depicted that nitrogen was found 277.5 kg/ha, 421.5 kg/ha, 457.15 kg/ha, phosphorus was found 15.5 kg/ha, 16.51 kg/ha 19.95 kg/ha and potassium was found 132.92 kg/ha, 125.44 kg/ha and 166.33 kg/ha respectively for forest ecosystem, alpine pasture ecosystem and agro ecosystem. Our study revealed that in general, the soils are nearly neutral in reaction, having no salt problem and fields in agro ecosystem where peas and pulses were planted possessed higher nitrogen contents (457.15 kg/ha) than forest and alpine ecosystem (277.5 kg/ha, 421.5 kg/ha) due to the fixation of atmospheric nitrogen besides other nutrients such as P, K, Na and Ca.